Event-Related Potential Responses to Beloved and Familiar Faces in Different Marriage Styles: Evidence from Mosuo Subjects - Wu, Haiyan; Luo, Li; Dai, Junqiang; Yang, Suyong; Wang, Naiyi; Luo, Yue-jia (Frontiers in Psychology, 2016)
Research on familiar face recognition has largely focused on the neural correlates of recognizing a beloved partner or family member. However, no research has explored the effect of marriage style on the recognition of a beloved partner’s face, especially in matriarchal societies. Here, we examined the time course of event-related potentials (ERP) in response to the face of a beloved partner, sibling, or unknown person in a sample of individuals from the matriarchal Mosuo tribe. Two groups were assessed: intermarriage and walking marriage groups (i.e., couples in a committed relationship who do not cohabitate during the daytime). In agreement with previous reports, ERP results revealed more positive VPP, N250, and P300 waveforms for beloved faces than sibling faces in both groups. Moreover, P300 was more positive for beloved partner versus sibling faces; however, this difference emerged at fronto-central sites for the walking marriage group and at posterior sites for the intermarriage group. Overall, we observed that marriage style affects the later stage processing of a beloved partner’s face, and this may be associated with greater affective arousal and familiarity.